2015
DOI: 10.1007/s11999-015-4268-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Changes in Composition in Response to Treatment of a Mouse Model of Osteogenesis Imperfecta Sex-dependent?

Abstract: Background Osteogenesis imperfecta (OI) is a genetic disease characterized by skeletal fragility and deformity. There is extensive debate regarding treatment options in adults with OI. Antiresorptive treatment reduces the number of fractures in growing oim/oim mice, an animal model that reproducibly mimics the moderate-to-severe form of OI in humans. Effects of long-term treatments with antiresorptive agents, considered for treatment of older patients with OI with similar presentation (moderate-tosevere OI) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…In contrast, surprisingly only females showed significantly elevated levels of TNFα and IL1α in serum. We also observed a tendency toward higher fracture rate in OIM males, a trend that has been reported in previous studies as well as in a human cohort [40, 41]. The sexual dimorphism in the OIM phenotype is therefore more prevalent during early adulthood, but some differences are already evident by 5 weeks of age prior to sexual maturation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, surprisingly only females showed significantly elevated levels of TNFα and IL1α in serum. We also observed a tendency toward higher fracture rate in OIM males, a trend that has been reported in previous studies as well as in a human cohort [40, 41]. The sexual dimorphism in the OIM phenotype is therefore more prevalent during early adulthood, but some differences are already evident by 5 weeks of age prior to sexual maturation.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies in OIM have pooled mice of both genders for evaluation of treatment approaches [42], and many have used animals of one gender only [24, 26, 4345]. As noted in other recent studies, there are indications of sex-related differences in OI that may affect response to treatment that should be taken into account in future studies, particularly those targeting adolescents and adults [41, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…The amide I band, used as the denominator to assess the matrix contribution, is influenced by the environment in which the vibrating carbonyl-bonds sit, and hence any change in the association of noncollagenous proteins 33 can alter the position and intensity of this band. The collagen cross-link maturity, which is also elevated in other OI models 14, 32, 37 , may suggest disorganization and/or over-modification of abnormal mutant collagen fibrils. This parameter, although controversial 34 is widely used to study bone material properties and has been shown to correlate to enzymatic cross-links determined by HPLC 17 .…”
Section: Discussionmentioning
confidence: 97%
“…Three separate regions from three different sections of each type of bone were analyzed resulting in 9 images/bone type. Isys4 software (Spectral Dimensions, MD, USA) was used to subtract the embedding media (PMMA), and the infrared images were analyzed to determine 5 FTIR outcome parameter: (1) mineral-to-matrix ratio (area ratio of [917–1180 cm −1 ]/[1588–1712 cm −1 ] peaks), which characterizes tissue mineral content based on the presence of phosphate and is directly related to ash weight 16 ; (2) carbonate-to-phosphate peak area ratio ([852–890 cm −1 ]/[917–1180 cm −1 ]), which, as detailed elsewhere 14 , characterizes the extent of carbonate substitution into the hydroxyapatite lattice; (3) collagen cross-link intensity ratio (1660 cm −1 /1690 cm −1 ), which is related to the ratio of non-reducible to reducible enzymatic collagen cross-links as determined by HPLC 17 ; (4) mineral crystallinity intensity ratio (1030 cm −1 /1020 cm −1 ), which is linked to crystal size and perfection of the hydroxyapatite crystals 16 ; and (5) acid phosphate substitution intensity ratio (1128 cm −1 /1096cm −1 ), which characterizes the extent of acid phosphate substitution into the mineral lattice 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The first reason is that there may exist sex-dependent differences in response to pharmaceutical intervention in several mouse models of OI, which is what Raggio and colleagues mentioned. (8) Another reason why we did not include the male mice is that the male mice usually show more activity, sometimes even fighting and biting each other, which may cause fractures resulting from the bone fragility in this severe mouse model of OI. Because our primary goal was to evaluate the effect of strontium ranelate on the fracture reduction in OI, we thought that the male mice might not be suitable for the study.…”
mentioning
confidence: 99%